Primate tourism : a tool for conservation? - Russon, Anne E.; Wallis, Janette; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
Primate tourism is a growing phenomenon, with increasing pressure coming from several directions: the private sector, governments, and conservation agencies. At the same time, some primate sites are working to exclude or severely restrict tourism because of problems that have developed as a result. Indeed, tourism has proven costly to primates due to factors such as disease, stress, social disruption, vulnerability to poachers, and interference with rehabilitation and reintroduction. Bringing together interdisciplinary expertise in wildlife/nature tourism and primatology, experts present and discuss their accumulated experience from individual primate sites open to tourists, formal studies of primate-focused tourism, and trends in nature and wildlife tourism. Chapters offer species- and site-specific assessments, weighing conservation benefits against costs, and suggesting strategies for the development of informed guidelines for ongoing and future primate tourism ventures. Primate Tourism has been written for primatologists, conservationists and other scientists. It is also relevant to tourists and tourism professionals.
List of contributors; Part I. Introduction: 1. Reconsidering primate tourism as a conservation tool: an introduction to the issues / Anne E. Russon and Janette Wallis; Part II. Asian Primates: 2. Tourism, infant mortality, and stress indicators among Tibetan macaques at Huangshan, China / Carol M. Berman, Megan D. Matheson, Jin-Hua Li, Hideshi Ogawa, and Consuel S. Ionica; 3. Provisioning and tourism in free-ranging Japanese macaques / Hiroyuki Kurita; 4. Proboscis monkey tourism: can we make it 'ecotourism'? / Heathor C. Leasor and Oliver J. Macgregor; 5. Orangutan tourism and conservation: 35 years' experience / Anne E. Russon and Adi Susilo; 6. The impact of tourism on the behavior of rehabilitated orangutans (Pongo abelii) in Bukit Lawang, North Sumatra, Indonesia / David F. Dellatore, Corri D. Waitt, and Ivona Foitovà; Part III. African Primates: 7. Lemurs and tourism in Ranomafana National Park, Madagascar: economic boom and other consequences / Patricia C. Wright, Benjamin Andriamihaja, Stephen J. King, Jenna Guerriero, and Josephine Hubbard; 8. Some pathogenic consequences of tourism for nonhuman primates / Robert M. Sapolsky; 9. Baboon ecotourism in the larger context / Shirley C. Strum and Deborah L. Manzolillo Nightingale; 10. Mountain gorilla tourism as a conservation tool: have we tipped the balance? / Michele L. Goldsmith; 11. Evaluating the effectiveness of chimpanzee tourism / James S. Desmond and Jenny A.Z. Desmond; Part IV. Neotropical Primates: 12. The impact of tourist group size and frequency on neotropical primate behavior in Tambopata, Peru / Chloe Hodgkinson, Christopher Kirkby and Eleanor J. Milner-Gulland; 13. Interactions between tourists and white-faced monkeys (Cebus capucinus) at Manuel Antonio National Park, Quepos, Costa Rica / Laurie Kauffman; 14. Effects of tourism on Ecuadorian primates: is there a need for responsible primate tourism? / Stella de la Torre; Part V. Broader Issues: 15. Economic aspects of primate tourism associated with primate conservation / Glen T. Hvenegaard; 16. Considering risks of pathogen transmission associated with primate-based tourism / Michael P. Muehlenbein and Janette Wallis; 17. Guidelines for best practice in great ape tourism / Elizabeth A. Williamson and Elizabeth J. Macfie; Part VI. Conclusion: 18. Primate tourism as a conservation tool: a review of the evidence, implications, and recommendations / Anne E. Russon and Janette Wallis; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Ecotourism -- Environmental aspects; Primates; Primates -- Habitat -- Conservation; Wildlife conservation; Electronic books